Transcatheter Closing Atrial Septal Defect in a Child With Hereditary Spherocytosis - Ji, Zhixian; Liu, Na; Du, Zhanhui; Luo, Gang; Bing, Zhen; Xing, Quansheng; Pan, Silin (Frontiers in Pediatrics, 2019)
A 3-year-old girl was admitted for the correction of artrial septal defect (ASD). Open heart operation with cardiopulmonary bypass is dangerous because the patient also had hereditary spherocytosis, which put her at risk for hemolytic anemia. Therefore, percutaneous transcatheter closure for ASD was chosen and performed successfully, which avoided the erythrocyte damage caused by cardiopulmonary bypass. This is the first time such a case has been reported, and we present an alternative approach for ASD with hereditary spherocytosis.